STUDY OF THE IMPACT OF FAMILY ENVIRONMENT OF HIGH SCHOOL LEVEL STUDENTS ON THEIR EDUCATIONAL ADJUSTMENT ABILITY - Shukla, Beena; Shroff, Sangeeta (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Education is a great necessity for the all-round development of a human being. Without education, complete development of any person is not possible. Education is the most important part of human life. Education is the ladder on which a person can raise his economic, social etc. levels. Education is the basis of the power of society. The computer era had started in the whole of India, which gradually started showing its effect in all sections, due to which computer knowledge became as important and mandatory as education for all sections. The most important resource for a nation or society is human being. Any nation can move forward towards progress only at that time. Whereas every human being should have the facility to develop himself freely to the extent he is capable of doing so. In fact, teaching occupies an important place in the history of human development.